TELAAH NORMATIF ATAS AKTA NOTARIIL DALAM TRANSAKSI EKONOMI SYARIAH - juni aziwantoro (PERADA, 2018)
Potential disputes can arise in sharia economic transactions if the parties do transaction that are not suitable with sharia principles, even though records have been made at the bank. Another factor is because one party default or does not carry out the contract stated in the notarial deed agreement. In this study, it was revealed that Islamic legal norms teach the importance of recording in muamalah. Thus, the Notarial deed in Islamic economic transactions is very important to guarantee the rights and obligations of the parties who made the agreement. Making the authentic deeds is done in order to create certainty, order, legal protection and to avoid future disputes.